98 The impact of music, play, pet, and art therapies in managing pain and anxiety in paediatric patients in hospital: a systematic review. (21st October 2022) - Goren, Katherine; Cen, Yuchen; Montemurri, Vanessa; Moodley, Dirusha; Sutton, Arielle; Ahmed, Alveena; Alphonsus, Lotus; Denezis, Peter; Fleming, Courtney; Guertin, Hailey; Hyland, Kiley; Kalim, Ayesha; et al.
Abstract: Background: The hospital can provoke significant feelings of pain, fear, and anxiety in children. Being in a new setting, often separated from loved ones and undergoing multiple medical procedures may elicit negative emotions. Complementary treatments may minimize these feelings and facilitate a more positive experience for children in hospital. Objectives: This systematic review aims to explore the impact of music, play, pet, and art therapy on pain and anxiety in paediatric patients in hospital. Design/Methods: Databases MEDLINE, CINAHL, Cochrane Library, and EMBASE were searched from database inception to November 2020 and reference lists were screened. Randomized control trials (RCTs) of paediatric patients evaluating the impact of music, pet, play, and/or art therapy on pain and/or anxiety were eligible for inclusion. Study setting was limited to the hospital (inpatient/outpatient) and/or emergency department. No restrictions were placed on the comparator. Duplicate studies were removed, and abstract and full-text screening was completed independently and in duplicate by reviewers. Reviewers extracted data from eligible studies into predeveloped REDCap forms independently and in duplicate. A narrative synthesis was used to summarize study findings using the synthesis without meta-analysis (SWiM) guidelines. Quality of evidence was then assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) across studies for each intervention and outcome. Results: 761 documents were identified and 30 RCTs were included, covering music (n=15), play (n=13), and pet (n=3) therapy. One study examined music and play therapy. No art therapy studies were identified. Studies took place in the inpatient setting (n=18), outpatient setting (n=5), a combination of both inpatient and outpatient (n=3), and the emergency department (n=4). Most studies (n=25, 83%) evaluated patients' pain and/or anxiety before, during, and/or after undergoing procedures in hospital such as surgery, venipuncture, and imaging. There was high certainty of evidence for play therapy in reducing pain and moderate certainty for music and pet therapy. Moderate certainty of evidence supported music and play therapy in reducing anxiety; however, pet therapy was found to have little to no significant difference. None of the interventions were found to increase pain or anxiety. Conclusion: Complementary therapies such as music, play, and pet therapy should be utilized in parallel to medical treatments in paediatric patients receiving care in hospital to mitigate pain and anxiety in addition to promoting a positive hospital experience.